变位系数与螺旋角对斜齿轮强度的影响 - 罗登峰; 乔永钦; 张建源; 刘冬敏 (Jixie chuandong)
Analysis of typical gear instance,the influence of the modification coefficient and the helix angle of gear strength is discussed,and a reference for the design of the helical gear is provided.